First-year practicum experiences for preservice early childhood education teachers working with birth-to-3-year-olds: An Australasian experience. Issue 4 (1st October 2016) - White, E. Jayne; Peter, Mira; Sims, Margaret; Rockel, Jean; Kumeroa, Maureen
ABSTRACT: This article reports on a project, "Collaboration of Universities Pedagogies of Infants' and Toddlers' Development—'down under' (CUPID), " in which the practicum experiences of 1st-year preservice initial teacher education (ITE) students at five universities across Australia and New Zealand (NZ) engaging in early childhood education (ECE) teacher programs were evaluated as part of a larger longitudinal project. The results from year 1 of their qualification experiences highlight the diverse and complex approaches to practicum experiences, ranging from specialized events with birth-to-3-year-olds to generic practicum with a wider age group. The implications of the practicum experience, in its many iterations, are explored in terms of the treatment of infant and toddler pedagogy as a specialization, and as an integrated component of the curriculum. While an assumption appears to exist that infant and toddler specialization is optimum, the early results of this study, at end of year 1 of the qualification, suggest that associated practicum experiences are not consistently offered to 1st-year students in this domain nor is a pedagogy specialism for this age group promoted. This article speculates on the reasons why this phenomenon occurs, the limitations and potentialities such a view upholds, and the implications for teachers in their work with birth-to-3-year-olds in the current policy context of both countries.